The World Bank Pension Conceptual Framework - World Bank (Washington, DC, 2012)
Since the mid 1980's, the World Bank has responded to the need to strengthen social insurance and contractual savings systems providing old age income support in developing countries. Such support has also been driven by pressures of global population aging, the erosion of informal and traditional family support systems, and weaknesses in the governance and administration of existing pension systems. The importance of effective formal sources of retirement income is accentuated by changes in work and family patterns including the increasing participation of women in formal employment, rising divorce rates, diminishing job stability and increases in local and international labor migration. The Bank's conceptual framework has emerged from its experience in Bank-supported reforms and the changing conditions and needs in client countries. Following the important work of the mid-1990's, averting the old age crisis that established key principles and concepts, the Bank's attention has increasingly focused on refining system designs to adapt these principles to widely varying conditions and better address the needs of diverse populations to manage the risks in old age.